Reviewing Issues And Challenges Faced By Corporate Governance At The Time Of PANDEMIC (Journal of Namibian Studies : History Politics Culture, 2023)
The widespread outbreak of coronavirus (COVID-19) poses a significant risk to human life. Companies throughout the world are facing extinction because of the epidemic, which has caught the attention of regulators and corporate governance experts. In this research, we examine the role that good corporate governance practices play in ensuring that businesses are able to weather the COVID-19 storm. COVID 19 The pandemic has had not only human but also severe economic effects throughout the world. Due to complications with things like meetings, dividends, liquidity, disclosure, capital allocation, risk management, and internal control, it poses a threat to the profitability of a company's day-to-day operations and poses a threat to shareholders as well. Companies should be allowed to have a hybrid AGM. Businesses have been prompted to speed up the process of establishing a solid technological foundation as a result. In times of economic turmoil, management should evaluate share repurchase plans. Executive compensation is a key area for the Remuneration Committee to focus on.